TAHU MENGHAMBAT KEHILANGAN TULANG LUMBAR TIKUS BETINA OVARIEKTOMI [Tofu Attenuates Lumbar Bone Loss of Ovariectomized Female Rats] - Samsu Udayana Nurdin; Deddy Muchtadi; Ita Djuwita; Suyanto Pawiroharsono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
The objectives of this research were to examine the efeects of feed containing soybean tofu and tempeh on lumbar bone density and mass of ovariectomized female rats. Twenty four 17 weeks-old Sprague-Dawley rats were randomly assigned to four group, i.e.: (1) non-ovariectomized rats fed casein based diet (NonOvx), (2) ovariectomized rats fed casein based diet (OvxC), (3) ovariectomized rats fed diet containing soybean tofu (OvxH), and (4) ovariectomized rats fed diet containing soybean tempeh (OvxT); in three block based on their body weight. The result show that body weight gram of ovariectomized rats was greater than nonovariectomized. Ovariectomy caused atrophy of the uterus, and resulted in higher serum calcium level. The lower lumbar vertebrae density of ovariectomized rats was observed and the decrease was prevented by tofu.